Antibiotic Susceptibility of Neisseria gonorrhoeae Isolates from Guangzhou, China, during 2002–2011 - Zheng, Heping; Yang, Bin; Wu, Xingzhong; Huang, Jinmei; Zeng, Weiying; Xue, Yaohua; Qin, Xiaolin; Lan, Yinyuan; Tang, Sanmei; Ou, Jiangli; Li, Yixin (Japanese Journal of Infectious Diseases, 2014)
Antibiotic susceptibility of Neisseria gonorrhoeae in Guangzhou during 2002–2011 showed that resistance to penicillin and ciprofloxacin was high, while ceftriaxone remained effective although there was a trend towards reduced sensitivity.